Factors Influencing the Customer Dining Experience and Retention at Marrybrown in Malaysia - Oh, Zi Jian; Utama, Anak Agung Gde Satia; Ong, Wen Huey; Kee, Daisy Mui Hung; Mane, Gandhar; Ganatra, Varsha; Oh, Jinzun; Ong, Li Zhen; Munisvarar, Prabawathy A/P Arulanantha (AIBPM Publisher, 2021)
Marrybrown is a Malaysian brand that develops steadily in Halal fast-food chains, which deliver great value products and exceptional quality service. Marrybrown has utilized its competitive advantages and successfully sustained itself among the competitors in the same market. This study investigates the factors influencing the customer dining experience and retention at Marrybrown in Malaysia. The research method is an online survey and analyzed using V-ONE. The findings indicated that food quality, location preference, menu innovation, restaurant environment, and service quality are important variables that affect the customer dining experience and customer retention at Marrybrown located in Malaysia. The findings provide suggestions for future research and improvement of the services provided by Marrybrown located in Malaysia.